Possibilities for Real-time DFA Based Injury Detection and Skill Level Differentiation. (2016) - Norris, M.; Kenny, I.C.; Healy, R.; Anderson, R.
Abstract: Detrended fluctuation analysis (DFA) is applied to running stride time series for the detection of long range correlations. However, there is no concurrent real-time data collection and DFA feedback mechanism. We aimed to verify a running analysis system for production of real-time DFA α values. Data were collected utilising an accelerometer, attached to the tibia. The accelerometer data were transmitted to MATLAB for processing. Results demonstrated DFA α value output < 2 seconds post individual running Epochs, and < 5 seconds post run completion. Our running analysis system provides rapid advanced variability information, important in both training, and injury prevention.